IMPROVING STUDENTS™ READING COMPREHENSION ACHIEVEMENT IN NARRATIVE TEXT THROUGH EXPERIENCE- TEXT- RELATIONSHIP (ETR) METHOD - Samosir, Dessy Natalia; -, Meisuri (TRANSFORM: Journal of English Language Teaching and Learning, 2013)
ABSTRACT This study focuses on the improvement of students™ reading comprehension achievement in narrative text through Experience-Text-Relationship (ETR) Method. This study deals with   classroom action research which was done in 6 meetings. The subject of this study was the second grade of SMP N 41 Medan, class VIII5. One class is totally taken as the subject of this study. The number of the sample is 34 students. The data of this study were obtained from the reading test, observation sheet, and diary notes. Based on the analysis data, it was found that the students™ achievement improved from the orientation test, test cycle I, and test cycle II. The findings of this study indicated that Experience- Text- Relationship (ETR) Method improved the students™ reading comprehension achievement. The students™ mean scores showed significant improvement, the mean of Cycle I = 64, 38 and the mean of Cycle II = 77, 20. Keywords: Reading Comprehension, Narrative Text, Experience-Text-Relationship (ETR) Method